Bibliometric Analysis of Scopus-Indexed Waqf Studies - Aam Slamet Rusydiana (Ekonomi Islam Indonesia, 2019)
This study aims to determine the development map of waqf research that is indexed by Scopus. The research was conducted in November 2019 by searching through the Scopus database with the keyword "waqf". The data analyzed were 104 publications of Scopus indexed waqf research publications. The development map of waqf research is obtained through the export process into the .txt file format. The export data is then processed and analyzed using the VOSviewer application program to find out the bibliometric map of the development of waqf research that is indexed by Scopus. The results showed that the number of publications on the development of waqf research indexed Scopus from 2010-2019 experienced a significant increase and the most were published in ISRA International Journal of Islamic Finance. Network visualization showed that the map of the development of waqf research was divided into 5 clusters. Cluster 1 consists of 10 topics, cluster 2 consists of 10 topics, cluster 3 consists of 5 topics, cluster 4 consists of 5 topics, and cluster 5 consists of 3 topics. The author who published the most research results in the field of waqf was Hidayatul Ihsan. In addition, the largest contributor to the publication of waqf research that indexed by Scopus is the Faculty of Economics and Muamalat Universiti Islam Malaysia, Institute of Islamic Banking and Finance, International Islamic University Malaysia.